Microscopy‐based assay for semi‐quantitative detection of SARS‐CoV‐2 specific antibodies in human sera: A semi‐quantitative, high throughput, microscopy‐based assay expands existing approaches to measure SARS‐CoV‐2 specific antibody levels in human sera. (30th December 2020) - Pape, Constantin; Remme, Roman; Wolny, Adrian; Olberg, Sylvia; Wolf, Steffen; Cerrone, Lorenzo; Cortese, Mirko; Klaus, Severina; Lucic, Bojana; Ullrich, Stephanie; Anders‐Össwein, Maria; Wolf, Stefanie; et al.
Abstract: Emergence of the novel pathogenic coronavirus SARS‐CoV‐2 and its rapid pandemic spread presents challenges that demand immediate attention. Here, we describe the development of a semi‐quantitative high‐content microscopy‐based assay for detection of three major classes (IgG, IgA, and IgM) of SARS‐CoV‐2 specific antibodies in human samples. The possibility to detect antibodies against the entire viral proteome together with a robust semi‐automated image analysis workflow resulted in specific, sensitive and unbiased assay that complements the portfolio of SARS‐CoV‐2 serological assays. Sensitive, specific and quantitative serological assays are urgently needed for a better understanding of humoral immune response against the virus as a basis for developing public health strategies to control viral spread. The procedure described here has been used for clinical studies and provides a general framework for the application of quantitative high‐throughput microscopy to rapidly develop serological assays for emerging virus infections.